0
$\begingroup$

I have to compute the general solution and compute the solution given an initial value.

$ y'' + 3y' + 2y = t^2 $

$ y(0) = y'(0) = 0$

I understand the first thing I need to do is find the homogeneous equation solution.

$ y'' + 3y' + 2y = 0 $

Solving this gives me

$ y_h(t) = k_1e^{-2t} + k_2e^{-t} $

So my next step is finding the particular solution. So I need to find $ y_p(t) $.

I assume $y_p(t) = at^2$ since there is a $t^2$ on the right hand side of the initial equation.

So now I have:

$ y_p = at^2 $

$ y_p^{'} = 2at $

$ y_p^{''} = 2a $

So I plug this into the original equation and am given

$ 2a + 3(2at) + 2(at^2) = t^2 $$\rightarrow$$ 2a + 6a + 2at^2 = t^2$

Thus $ a = $$\frac{1}{2}$$ $ since $ 2at^2 = t^2 $

So now I go on to get the general solution: $ y(t) = k_1e^{-2t} + k_2e^{-t} + $$\frac{1}{2}$$t^2 $

and the derivative is $ y'(t) = -2k_1e^{-2t} + -k_2e^{-t} + t $

When I solve for $ k_1 $ and $ k_2 $ both are equal to zero (0). I am not sure whether this is right or not because then I am only left with $ y(t) = $$\frac{1}{2}$$t^2 $

I am just looking for someone to look over my work I am not sure whether this is right or not.

$\endgroup$
1
$\begingroup$

the particular solution should be $$y_p=At^2+Bt+C$$

$\endgroup$
  • $\begingroup$ Why? I thought we only needed t^2. $\endgroup$ – Andy Cohen Apr 25 at 21:57
  • $\begingroup$ This according to the undetermined coefficient method $\endgroup$ – E.H.E Apr 25 at 21:58
  • 2
    $\begingroup$ There is a chart at Paul's Online Notes that gives the form of the initial guess for $y_p$. $\endgroup$ – John Wayland Bales Apr 25 at 22:01
0
$\begingroup$

You might notice that smaller powers appears when you take the derivative of $t^2$. So when you plug this in, your equation turned out to be

$$ 2a + 6at + 2at^2 = t^2 $$

You need this to be true for all $t$. This isn't possible, since even if $a = \frac12$, you're left with

$$ 1 + 3t = 0 $$

which obviously isn't true for all $t$.

The way to fix this is to add smaller powers of $t$ in your guess:

$$ y_p(t) = at^2 + bt + c $$

plugging this in gives

$$ (2a + 3b + 2c) + (6a + 2b)t + 2at^2 = t^2 $$

Now you can match the 3 coefficients to produce a system of equations

\begin{align} 2a &= 1 \\ 6a + 2b &= 0 \\ 2a + 3b + 2c &= 0 \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.